Copper adorned magnetic nanoparticles as a heterogeneous catalyst for Sonogashira coupling reaction in aqueous media - Sheikh, Safoora; Nasseri, Mohammad Ali; Allahresani, Ali; Varma, Rajender S (Scientific reports, 2022)
A nanomagnetic hydrophilic heterogeneous copper catalyst, termed γ-Fe2O3@PEG@PAMAM G0-Cu, has been successfully prepared and characterized using FT-IR, XRD, FE-SEM, TEM, EDX, mapping, TGA/DTG, VSM and ICP analyses. The catalyst displayed excellent activity for the palladium-free Sonogashira cross coupling reaction of various aryl iodides and bromides with phenylacetylene derivatives in pure water. The presence of polyethylene glycol coupled with hydrophilic character of the Cu-catalyst adorned on γ-Fe2O3 MNPs provides the ready dispersion of the catalyst particles in water, leading to higher catalytic performance as well as facile catalyst recovery via simple magnetic decantation. The recovered catalyst was reused for at least six successive runs with little reduction in its catalytic activity and any noticeable changes in its structure. The use of water as a green solvent, without requiring any additive or organic solvent, as well as the exploitation of abundant and low-cost copper catalyst instead of expensive Pd catalyst along with the catalyst recovery and scalability, make this method favorable from environmental and economic points of view for the Sonogashira coupling reaction.
Keywords: Bromides; magnetické nanočástice; Spectroscopy, Fourier Transform Infrared; Copper; měď; Iodides; jodidy; Polyethylene Glycols; spektroskopie infračervená s Fourierovou transformací; Water; Solvents; Magnetite Nanoparticles; rozpouštědla; polyethylenglykoly; bromidy; voda